The Influence of Individual Career and Individual-Organization Fit on Generation Z's Intention to Quit Work - Achmad Zaki Firmansyah; Nafia Ilhama Qurratu’aini; Jeziano Rizkita Boyas; Wahyu Eko Pujianto (Al-Qalam Institue, 2026)
This study examines the influence of Individual Career and Person–Organization Fit on Generation Z employees’ Turnover Intention, with Job Satisfaction as a mediating variable. A quantitative cross-sectional explanatory design was employed. Data were collected through an online questionnaire from 210 Generation Z employees aged 19–28 years working in Sidoarjo Regency, Indonesia, using purposive sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 was applied for data analysis. The findings show that Individual Career and Person–Organization Fit significantly and positively influence Job Satisfaction and Turnover Intention. Job Satisfaction also has a significant positive effect on Turnover Intention and mediates the relationships between Individual Career, Person–Organization Fit, and Turnover Intention. These results indicate that Generation Z employees with stronger career orientation and greater organizational value congruence remain willing to seek alternative career opportunities despite experiencing higher job satisfaction. The study concludes that effective retention strategies should integrate career development, organizational value alignment, and meaningful work experiences to enhance employee commitment, workforce sustainability, organizational competitiveness, and long-term human resource effectiveness.